A comparison of dimensional standard of several nickel-titanium rotary files - Ki-Won Kim; Kyung-Mo Cho; Se-Hee Park; Ki-Yeol Choi; Bekir Karabucak; Jin-Woo Kim (Korean Academy of Conservative Dentistry, 2014)
Objectives The aim of this study was to compare the dimensional standard of several nickel-titanium (Ni-Ti) rotary files and verify the size conformity. Materials and Methods ProFile (Dentsply Maillefer), RaCe (FKG Dentaire), and TF file (SybronEndo) #25 with a 0.04 and 0.06 taper were investigated, with 10 in each group for a total of 60 files. Digital images of Ni-Ti files were captured under light microscope (SZX16, Olympus) at 32×. Taper and diameter at D1 to D16 of each files were calculated digitally with AnalySIS TS Materials (OLYMPUS Soft Imaging Solutions). Differences in taper, the diameter of each level (D1 to D16) at 1 mm interval from (ANSI/ADA) specification No. 101 were statistically analyzed using one-way ANOVA and Scheffe's post-hoc test at 95% confidence level. Results TF was the only group not conform to the nominal taper in both tapers (p < 0.05). All groups except 0.06 taper ProFile showed significant difference from the nominal diameter (p < 0.05). Conclusions Actual size of Ni-Ti file, especially TF, was different from the manufacturer's statements.